SAMPLE SURVEY ON THE USE OF CONTRACEPTIVE DRUGS AMONG FEMALE STUDENTS IN AHMADU BELLO UNIVERSITY, ZARIA - Mohammed, Aminu Suleiman; Suleiman, Abdulrazaq; Abdullahi, Jamila; Kargi, Isah Aliyu; Elisha, Handan T. (FUDMA Journal of Sciences, 2026)
The use of contraceptive drugs is a vital component of reproductive health, especially among young women who are at a stage in life where they must make important decisions about their bodies, education, and future. Understanding the awareness, attitudes, and usage patterns of contraceptive drugs among this population is important because students in higher education often face increased exposure to new ideas, peer influences, and social pressures. A descriptive cross-sectional survey design was adopted, and data was collected through structured self-administered questionnaires distributed to 116 female students across different faculties. Chi-square (χ²) tests was employed to examine associations between socio-demographic factors and contraceptive use. The results revealed that awareness of contraceptives was high (90.5%), but only 37.1% had ever used them and just 9.5% were current users. Prevention of pregnancy (53.5%) was the main reason for use, while fear of side effects (35%) and cultural/religious concerns (24%) were the primary reasons for non-use. Attitudinal responses showed that while most students acknowledged the role of contraceptives in preventing unwanted pregnancies (73.2%), a considerable number still associated them with immorality. Chi-square analysis further showed that marital status (p = 0.001) and awareness (p = 0.019) were significantly associated with contraceptive use, while age and academic level were not. The study concludes that although knowledge and awareness are widespread, actual usage remains low due to stigma, and cultural influences. It recommends intensifying reproductive health education, peer sensitization, and confidential access to contraceptives to bridge the gap between awareness and practice among female students.
Keywords: Contraceptive Drugs; Reproductive Health; Chi-Square Test; Cultural Influences